2019
DOI: 10.1016/j.ygcen.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Direct actions of adiponectin on changes in reproductive, metabolic, and anti-oxidative enzymes status in the testis of adult mice

Abstract: Obesity is a major health problem that is linked to decreased sperm count. It is hypothesized that an obesity-associated reduction in adiponectin secretion may be responsible for impairment of spermatogenesis. Therefore, the aim of the study was to evaluate the direct role of adiponectin in spermatogenesis and steroid synthesis in adult mice. This study showed that adiponectin receptors (AdipoR1 and AdipoR2) were localized in Leydig cells and seminiferous tubules in the testis of adult mice. The result of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…Adiponectin regulates both spermatogenesis and steroidogenesis in adult testis via its two receptors, AdipoR1 and AdipoR2 [89,99]. Indeed, in vitro experiments showed that adiponectin acted directly in Leydig cells to decrease androgen secretion, which was associated with inhibition of the StAR protein in Leydig cells [94].…”
Section: Expression Regulation and Effect Of Adiponectin In Gonadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin regulates both spermatogenesis and steroidogenesis in adult testis via its two receptors, AdipoR1 and AdipoR2 [89,99]. Indeed, in vitro experiments showed that adiponectin acted directly in Leydig cells to decrease androgen secretion, which was associated with inhibition of the StAR protein in Leydig cells [94].…”
Section: Expression Regulation and Effect Of Adiponectin In Gonadsmentioning
confidence: 99%
“…However, adiponectin did not modulate anti-Mullerian hormone (AMH) transcript levels [101]. Another important role of adiponectin is to maintain insulin sensitivity by stimulating glucose uptake in the testes [99]. Indeed, intratesticular glucose level was shown to be associated with testicular functions like testosterone production [102].…”
Section: Expression Regulation and Effect Of Adiponectin In Gonadsmentioning
confidence: 99%
“…61 Lactate produced in the Sertoli cells is transported to the germ cells and prevent apoptosis. 62 These findings thus suggest that treatment with genistein increases production of antioxidant enzymes and lactate which contributes to suppress germ cell apoptosis and improves spermatogenesis in T2D mice.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, GH-induced insulin/IGF family of growth factors activates glucose transporter 8 (GLUT8) which helps in chronological conversion of glucose into lactate by mature Sertoli cells [79,80]. Notably, lactate is a preferred energy metabolite serving the energy requirement for proper testicular functioning and development of spermatogenic cells [81][82][83]. Also, the Figure 1.…”
Section: Impact Of Gh/insulin/igf-1 Signaling In the Regulation Of Tementioning
confidence: 99%